TALIA, the first agricultural virtual extension agent operated entirely by AI - CGIAR Platform for Big Data in Agriculture (2021)
We created a small prototype that we tested among partners using Telegram. We feel that Watson has true potential to build a complete agricultural assistant to support farmers, however it is a complex endeavor where in-depth experience with Watson is required.